Effect of Financial Literacy and Quality of Accounting Information on Investment Interest with Cryptocurrency as a Variable Intervening - Baihaqi Ammy (Enrichment : Journal of Management, 2022)
This study is a research conducted to determine the effect of financial literacy and quality of accounting information on investment interest mediated by cryptocurrencies in Accounting Study Program students, FEB UMSU. This study uses a quantitative approach with primary data sources obtained from the distribution of questionnaires. The sampling technique in this study is using the slovin technique, with the number of objects being 100 respondents. The analysis carried out in this study includes path analysis using the PLS application. Based on the results of the study, it was concluded that Financial Literacy has an effect on Cryptocurrency in Accounting Study Program students FEB UMSU, Quality of Accounting Information affects Cryptocurrency in Accounting Study Program students FEB UMSU, Financial Literacy affects Investment Interest in Accounting Study Program students FEB UMSU, Quality of Accounting Information affects Interest Investment in Accounting Study Program FEB UMSU Students, Cryptocurrency does not intervene in the influence of Financial Literacy on Investment Interest in Accounting Study Program students FEB UMSU and Cryptocurrency intervenes in the influence of Accounting Information Quality on Investment Interest in Accounting Study Program students FEB UMSU.